Effect of temperature on survival of Australian entomopathogenic nematodes and their virulence against the Queensland fruit fly, Bactrocera tryoni - Sitaram Aryal; Uffe N. Nielsen; Nanette H. Sumaya; Craig Wilson; Markus Riegler (BioControl, 2022)
Entomopathogenic nematodes (EPNs) are commonly used biocontrol agents of insect pests, with a wide range of commercially available isolates targeting specific pests. New isolates are, however, required to improve pest control across a wider range of environmental conditions for target pests, including emerging threats. We assessed the effect of temperature on survival and virulence of 17 Australian isolates of five EPN species ( Heterorhabditis bacteriophora , Heterorhabditis indica , Heterorhabditis marelatus , Heterorhabditis zealandica and Steinernema feltiae ) against larvae and pupae of the Queensland fruit fly, Bactrocera tryoni . All isolates still infected and killed larvae after infective juveniles (IJ) had been kept without insect hosts at 15 °C, 25 °C or 30 °C for two weeks, indicating their potential to remain viable under field conditions. However, the mean LD 50 value ranged from 35 to 150 and was generally lower at 15 °C than at 25 °C and 30 °C. Similarly, after IJs had been kept at 25 °C for 1–3 weeks without insect hosts, all isolates infected B. tryoni larvae, with mean LD 50 values ranging from 25 to 144. Interestingly, 15 isolates infected and killed B. tryoni pupae after one week, with a mean LD 50 value between 130 and 209, but only two isolates after two weeks, with a mean LD 50 value between 229 to 209. No pupal mortality was seen after three weeks. In absence of hosts, EPNs survived longer at 15 °C and 25 °C than at 30 °C. Complete EPN mortality occurred after nine weeks at 30 °C, and after 18 weeks at 15 °C and 25 °C, except for some survival in one S. feltiae isolate (Sf.ECCS). Overall, six isolates of H. indica (Hi.HRN2, Hi.LMI2, Hi.QF6), H. bacteriophora (Hb.HIE), H. zealandica (Hz.NAR1) and S. feltiae (Sf.ECCS) performed best and need further testing as potential biocontrol agents against B. tryoni under semi-field and field conditions.

Isolation and molecular characterization of five entomopathogenic nematode species and their bacterial symbionts from eastern Australia - Sitaram Aryal; Uffe N. Nielsen; Nanette H. Sumaya; Stefano De Faveri; Craig Wilson; Markus Riegler (BioControl, 2022)

Improving biocontrol of black vine weevil (Otiorhynchus sulcatus) with entomopathogenic fungi in growing media by incorporating spent mushroom compost - Ralph Noble; Andreja Dobrovin-Pennington; Jean Fitzgerald; Katie Dew; Craig Wilson; Kyle Ross; Colin Perkins (BioControl, 2018)